Advanced flow and temperature measurements in a forced convection molten salt test loop. (1st September 2021) - Arora, Ojasvin; Lancaster, Blain; Yang, Se Ro; Vaghetto, Rodolfo; Hassan, Yassin
Highlights: Ultrasonic flow measurements are conducted in high-temperature molten salt. Optical Fiber Sensors are utilized to measure the fluid temperature profiles. Transient two-dimensional temperature profiles of the salt are generated. The molten salt front development is analyzed using temperature data. Abstract: The elevated temperatures and corrosive environment typical of molten salt reactors' operating conditions may pose challenges to flow and temperature measurements. Experimental measurements of these thermal–hydraulic parameters are paramount to advance the knowledge and understanding of the molten salts' behavior, and are necessary for the validation of system-level and computational fluid dynamics codes. An experimental test facility has been utilized to characterize the thermal–hydraulic behavior of typical molten salts under steady-state and transient, forced flow conditions, by employing innovative measurement methods. The use of the non-intrusive ultrasonic technology has been successfully deployed and validated within a wide range of flow conditions, at elevated temperatures (600 °C). Two-dimensional salt temperature fields have been reconstructed from the reading of a fine network of optical fiber distributed temperature sensors and thermocouple probes, providing information on the salt front transition velocity. The results obtained can be used to validate and advance specialized simulation codes.